Developing descriptive reading materials in EFL classes by utilizing the local culture - Nur Azizah; Rita Inderawati; Machdalena Vianty (Universitas Syiah Kuala, 2021)
This study aimed to develop instructional descriptive reading materials of Bangka local culture in Indonesia, which are valid, practical and have a potential effect for Tour and Travel Study Program students at a vocational school in Bangka Belitung Province. The developed product would be used as supplementary materials to fulfill the students’ needs. This study used the research design proposed by Akker (1999), covering the phases of analysis, design, evaluation, and revision modified by Tessmer (1993). The data were collected through questionnaires, semi-structured interviews, and a reading comprehension test. The data were analyzed quantitatively and qualitatively. In order to determine the validity, practicality, and potential effect of the developed product, a formative evaluation was conducted. Validity was evaluated in experts review related to the content, language, and instructional design. The result showed that the developed product reached a very high validity category with the average score of all aspects evaluated; it was 3.57. The practicality evaluated in one-to-one and small group evaluations were categorized as very high practicality since the average scores of both evaluations were 3.71 and 3.58. After trying out the field test, the developed product was considered to have a high potential effect since 73.91% of the students achieved the required passing grade. Therefore, it could be concluded that it is possible to use the developed product as supplementary materials for teaching reading for the intended students.